The Impact of Digitalization and Innovation Culture on Human Resource Productivity with Work Motivation Mediation in the Islamic Banking Sector of Bank Muamalat Indonesia Regional East Java - Fitri Cahyaning; Mardani , Ronny Malavia; Muhammad Ridwan Basalamah (LP2M IAIN Palopo, 2025)
Digital transformation and innovation culture are two strategic elements in strengthening human resource performance, particularly in the Islamic banking sector. This study aims to analyze the influence of digitalization and innovation culture on human resource productivity, with work motivation as a mediating variable. The study was conducted at Bank Muamalat Regional East Java using a quantitative approach with an explanatory design. A total of 110 respondents were randomly selected from the branch employee population. Data were analyzed using the Structural Equation Modeling (SEM) method based on AMOS. The results of the study indicate that digitization and innovation culture have a positive and significant effect on work motivation. Innovation culture has also been proven to have a direct and significant effect on human resource productivity. However, digitization and work motivation do not have a significant direct effect on productivity. Furthermore, the indirect paths from digitalization and innovation culture to productivity through work motivation are also not statistically significant. These findings indicate that the role of work motivation as a mediator in the relationship between digitalization and innovation culture on human resource productivity has not yet been strongly established in the context of Islamic banking under study.